다양한 코발트-살렌계 이산화탄소/에폭사이드 촉매의 개발 및 중합 - 김보은 (The Graduate School, Ajou University, 2010)
Ligand variation on a cobalt(III) complex of Salen-type ligand comprised of 1,2-cyclohexenediamine and salicylaldehyde bearing a methyl substituent on its 3-position and -[CMe(CH2CH2CH2N+Bu3)2] on its 5-position, which is a highly active catalyst for CO2/propylene oxide copolymerization, was carried out. Replacement of the methyl substituent on 3-position with bulky isopropyl group resulted in alteration of the binding mode, consequently lowering TOF significantly. Replacement with ethyl group preserved not only the binding mode but also the activity. Either replacement of tributylammonium unit with trihexylammonium or trioctylammonium or replacement of 1,2-cyclohexenediamino unit with -NC(Me)2CH2N- decreased the activity even though the binding mode was unaltered.
학위논문(석사)--아주대학교 일반대학원 :분자과학기술학과,2010. 2
Keywords: Carbon dioxide; Epoxide; Salen-cobalt complexes; Polymerization; 코발트-살렌계; 이산화탄소/에폭사이드 촉매